Sensibilidade estética no uso das tintas naturais : pensando a prática da educadora Maria Lucina Busato Bueno - Rizzi, Alessandra (2021)
Based on the practice of the educator and artist Maria Lucina Busato Bueno who dedicated herself to research on the artistic use of natural ink, we seek to analyze the aesthetic and pedagogical experience proposed by her in arts education in school. The research problem translates into the following question: How much can practices with natural ink in arts and education awaken or incite even more people to be sensible to their surroundings, especially to nature and to other individuals with whom they live with? The dissertation, taking as its model the proposal developed by the artist and professor Maria Lucina, aims to investigate the way that the use of natural ink can provide an experience that might permit creation, reflection and investigation of the students, and develop their aesthetic sensibility, exploring the senses of hearing, smell, touch, vision and taste in an integral way. Therefore, it seeks to promote the production of new knowledge as a way of fomenting creativity, sensibility and interdisciplinarity in the fields of arts and education. It is a qualitative research in arts and education, as defined by Fortin and Gosselin (2014), taking as main references texts, artistic work and other records of the professor and artist produced in interaction with her students. The dissertation presents the following topics: first, it explains the relation between art and education, and the emergence of the use of natural inks in arts; in the second topic, it presents Maria Lucina’s educational proposal concerning the use of natural inks in arts; in the third topic, it identifies and explores the aesthetic and pedagogical potential of the project of the artist and educator. The conclusion highlights that the research of the artist and professor Maria Lucina Busato Bueno is of great relevance to the fields of arts and pedagogy. The systematization of the process of production of natural ink and its use in pedagogical and artistic practices reveals not only the artist’s affection for the subject matter, but also her intense activity in research regarding this theme. Her work makes accessible to other educators the result of her effort, clarifies questions in relation to these processes and brings new elements that enable taking her proposal to the classroom, contributing to humanization through aesthetic sensibility for educators and students.